Attacking 22 entries in rugby union: running demands and differences between successful and unsuccessful entries. (28th December 2016) - Tierney, P.; Tobin, D. P.; Blake, C.; Delahunt, E.
Abstract : Global Positioning System (GPS) technology is commonly utilized in team sports, including rugby union. It has been used to describe the average running demands of rugby union. This has afforded an enhanced understanding of the physical fitness requirements for players. However, research in team sports has suggested that training players relative to average demands may underprepare them for certain scenarios within the game. To date, no research has investigated the running demands of attacking 22 entries in rugby union. Additionally, no research has been undertaken to determine whether differences exist in the running intensity of successful and unsuccessful attacking 22 entries in rugby union. The first aim of this study was to describe the running intensity of attacking 22 entries. The second aim of this study was to investigate whether differences exist in the running intensity of successful and unsuccessful attacking 22 entries. Running intensity was measured using meters per minute (m min −1 ) for (a) total distance, (b) running distance, (c) high‐speed running distance, and (d) very high‐speed running distance. This study provides normative data for the running intensity of attacking 22 entries in rugby union. Forwards achieved greater high‐speed running intensity in successful (3.6 m min −1 ) compared to unsuccessful (1.8 m min −1 ) attacking 22 entries. Forwards should try and achieve greater high‐speed running intensity in attacking 22 entries to increase the likelihood of successful outcomes during this period of gameplay.